ANALISIS PROSES PERSEDIAAN BARANG PT VARIA SRI CENDANA DEPARTEMEN STORE DENGAN MENGGUNAKAN FUZZY LOGIC MAMDANI - Sihura, Dekirius; Fajrin, Alfannisa Annurrullah (Computer Science and Industrial Engineering, 2021)
Fuzzy logic is an appropriate way to solve problems that are difficult to define using mathematical models. This study focuses on analyzing the use of goods so that goods are always available when needed. The purpose of this study is to analyze how many items should be provided and how many items will be used. To optimize the inventory of goods, this research method is carried out by direct observation and collecting data on the use of goods in July 2019 to December 2019 and analyzes the use of goods using fuzzy logic with the Mamdani method so as to find out how much goods must be provided for the use of goods in the month January 2020.